Matrigel coatings for Parylene sheath neural probes. Issue 2 (23rd March 2015) - Lee, Curtis D.; Hara, Seth A.; Yu, Lawrence; Kuo, Jonathan T. W.; Kim, Brian J.; Hoang, Tuan; Pikov, Victor; Meng, Ellis
Abstract: The biologically derived hydrogel Matrigel (MG) was used to coat a Parylene‐based sheath intracortical electrode to act as a mechanical and biological buffer as well as a matrix for delivering bioactive molecules to modulate the cellular response and improve recording quality. MG was loaded with dexamethasone to reduce the immune response together with nerve growth factor (NGF) and brain‐derived neurotrophic factor (BDNF) to maintain neuronal density and encourage neuronal ingrowth toward electrodes within the sheath. Coating the Parylene sheath electrode with the loaded MG significantly improved the signal‐to‐noise ratio for neural events recorded from the motor cortex in rat for more than 3 months. Electron microscopy showed even coverage of both the Parylene substrate and the platinum recording electrodes. Electrochemical impedance spectroscopy (EIS) of coated electrodes in 1× phosphate‐buffered saline demonstrated low impedance required for recording neural signals. This result was confirmed by in vivo EIS data, showing significantly decreased impedance during the first week of recording. Dexamethasone, NGF, and BDNF loaded into MG were released within 1 day in 1× phosphate‐buffered saline. Although previous studies showed that MG loaded with either the immunosuppressant or the neurotrophic factor cocktail provided modest improvement in recording quality in a 1‐month in vivo study, the combination of these bioactive molecules did not improve the signal quality over coating probes with only MG in a 3‐month in vivo study. The MG coating may further improve recording quality by optimizing the in vivo release profile for the bioactive molecules. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 357–368, 2016.